1998
DOI: 10.1210/en.139.4.2102
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Regression of MCF-7 Xenografts in Nude Mice Treated with the Vitamin D3 Analog, EB1089

Abstract: 1,25-Dihydroxyvitamin D3 [1,25-(OH)2D3] and its synthetic analog EB1089 induce characteristic morphological features of apoptosis in MCF-7 cells in vitro that coincide with up-regulation of clusterin and cathepsin B, proteins associated with apoptosis in the mammary gland, and with down-regulation of Bcl-2, an antiapoptotic protein. To determine whether vitamin D3 compounds could mediate apoptosis of breast tumors in vivo, we treated nude mice carrying established MCF-7 xenografts with the low calcemic vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 0 publications
2
74
0
Order By: Relevance
“…26 Effects of vitamin D and analogues have been reported in early initiation and promotion phases of cancer development 44,45 as well as in late phases when used as a chemotherapeutic agent. 46 To overcome these problems, repeated measurements at different time points before diagnosis would be most valuable.…”
Section: Discussionmentioning
confidence: 99%
“…26 Effects of vitamin D and analogues have been reported in early initiation and promotion phases of cancer development 44,45 as well as in late phases when used as a chemotherapeutic agent. 46 To overcome these problems, repeated measurements at different time points before diagnosis would be most valuable.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that vitamin D analogs, through altered transcription of target genes, increase generation of ceramide and cPLA 2 activation such that apoptosis can be initiated in response to suboptimal concentrations of TNFa Vitamin D analogs, TNFa and apoptosis in breast cancer cells G Pirianov et al xenografts in nude mice. 31 The novel vitamin D analog CB1093 has been shown to display potent antitumor effects in vivo and in vitro and its effects on induction of apoptosis are evident at concentrations approximately tenfold lower than EB1089. 10 Furthermore, induction of apoptosis has been reported to be accompanied by decreased bcl-2 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…in breast cancer cells (43 (38). Vitamin D-stimulated apoptotic regression in mice bearing MCF-7 xenografts was also described (49). The underlying mechanism of the antiproliferative effects of 1,25-(OH) 2 D 3 on HC11 cells has yet to be clarified.…”
Section: Vitamin D and Breast Cancermentioning
confidence: 99%